Relationship between growth mindset and self-rated health in Chinese college teachers: sequential mediating effect of health self-efficacy and physical exercise - Yu, Tao; Zeng, Change; He, Lidong; Ying, Hu; Liu, Jie; Wu, Yuzhen; Li, Jiayuan; Guo, Yaxing; Chen, Yanjun; Pan, Xiaofu (Frontiers in Public Health, 2025)
BackgroundChinese college teachers’ health issues have become increasingly significant, making it crucial to promote their physical health. Based on self-regulation theory, this study aims to explore the relationship and underlying mechanisms between Chinese college teachers’ growth mindset of health and their self-rated health.MethodsThe study involved 456 Chinese college teachers (213 males, 243 females) who filled out a questionnaire measuring their growth mindset of health, health self-efficacy, physical exercise, and self-rated health.ResultsThe correlation analysis revealed positive links among Chinese college teachers’ growth mindset of health, health self-efficacy, physical exercise, and self-rated health. Further regression analysis indicated that their growth mindset of health positively influenced self-rated health, mediated by health self-efficacy and physical exercise.ConclusionThis study discovered a positive link between Chinese college teachers’ growth mindset of health and their self-rated health. It also emphasized the sequential mediating effect of health self-efficacy and physical exercise in this correlation, offering theoretical grounding and valuable insights for promoting college teachers’ physical health.